Does state control affect managerial incentives? Evidence from China's publicly listed firms - Lin, Chen; Su, Dongwei (Journal of Business Economics and Management, 2009)
Using data for 1203 publicly listed firms in China during 1999–2002, this paper empirically investigates whether and to what extent state control affects managerial incentives, including managerial compensation and CEO turnover. The paper finds that CEO turnover is negatively related to both current and lagged firm performance as measured by ROA and RPE (Relative Performance Evaluation) for non‐state‐controlled firms, while insensitive to performance measures for state‐controlled firms. In addition, CEO compensation is positively related to firm performance, but state ownership and control weaken this positive relation. Moreover, state control reduces the effectiveness of internal governance mechanisms such as the board of directors and supervisory committee. Overall, empirical results in the paper indicate that state ownership and control weaken managerial incentives and internal monitoring among publicly listed firms in China.First Publish Online: 14 Oct 2010